PERAN DUKUNGAN SOSIAL DALAM PELAKSANAAN PROGRAM PENDAMPINGAN IBU HAMIL DI 7 KABUPATEN/KOTA DI INDONESIA - Novianti Novianti; Suparmi Suparmi (IAKMI South Tangerang Branch, 2021)
Abstract Background: Reducing the Maternal Mortality Rate (MMR) is a priority target for the Indonesian government. The intervention research on the model of mentoring pregnant women by students is expected to encourage increased knowledge of pregnant women and the utilization of maternal and child health services. Objectives: this study aims to explore and analyze the role of social support as one of the important factors that support the success and acceptance of students’ mentoring program. Methods: Mentoring research was carried out in 2018 in 7 districts/cities of mentoring locus areas in Indonesia. The research was conducted with a qualitative approach using in-depth interviews and qualitative informants were selected purposively. Results: Social support from students and cadres is complementary in the process of mentoring pregnant women, support from husbands and families also plays a role in accepting student assistance programs for pregnant women. While the support from health workers, such midwives, both primary healthcare midwives and village midwives, is still very limited and has not been felt in this mentoring activity, there are still good opportunities for further improvement. The form of support given to pregnant women is in the form of knowledge, moral support, appropriate decision support from the family, and support for quality health care practices in antenatal care, delivery, and post-partum (postpartum). Conclusion: Social support in assisting pregnant women can be found from various actors and in various forms of support and is expected to contribute and support improving the quality of services for pregnant women Keywords: mentoring pregnant women, program evaluation, social support, health intervention Abstrak Latar Belakang: Penurunan Angka Kematian Ibu (AKI) menjadi target prioritas pemerintah Indonesia. Penelitian intervensi model pendampingan ibu hamil diharapkan dapat mendorong peningkatan pengetahuan ibu hamil dan pemanfaatan pelayanan kesehatan ibu dan anak. Tujuan: penelitian ini bertujuan untuk mengetahui dan menganalisa peran dukungan sosial menjadi salah satu faktor penting yang menunjang keberhasilan dan penerimaan program. Metode: Penelitian pendampingan dilaksanakan pada tahun 2018 di 7 Kabupaten/Kota wilayah lokus pendampingan di Indonesia. Penelitian dilakukan dengan pendekatan kualitatif menggunakan metode wawancara mendalam dan informan kualitatif dipilih secara purposif. Hasil: Dukungan sosial dari mahasiswa dan kader sifatnya saling melengkapi dalam proses pendampingan ibu hamil, dukungan dari suami dan keluarga juga berperan dalam penerimaan program pendampingan mahasiswa kepada ibu hamil. Sedangkan dukungan dari tenaga kesehatan yaitu bidan baik bidan puskesmas dan bidan desa masih sangat terbatas dan belum dirasakan dalam kegiatan pendampingan ini namun masih ada peluang yang baik untuk ditingkatkan selanjutnya. Bentuk dukungan yang diberikan kepada ibu hamil berupa dukungan pengetahuan, moral, dukungan keputusan yang tepat dari keluarga, serta dukungan praktik layanan kesehatan yang berkualitas dalam proses pemeriksaan kehamilan, persalinan, hingga pasca salin (masa nifas). Kesimpulan: Dukungan sosial dalam pendampingan ibu hamil dapat ditemukan dari berbagai aktor dan dalam berbagai bentuk dukungan dan diharapkan dapat berkontribusi dan mendukung peningkatan kualitas layanan pada ibu hamil. Kata Kunci : Pendampingan ibu hamil, evaluasi program, dukungan sosial, intervensi kesehatan.